Model to Predict Overall Survival in Patients With Hepatocellular Carcinoma After Curative Hepatectomy - Zhang, Li-xiang; Luo, Pan-quan; Chen, Lei; Song, Dong-da; Xu, A-man; Xu, Peng; Xu, Jia (Frontiers in Oncology, 2021)
Background. It is still a problem about the prognostic prediction after radical resection of hepatocellular carcinoma (HCC). In this paper, we established a model for the prognostic of HCC. Methods. 560 patients with curative HCC at our hospital from January 2007 to January 2014 have been included in our research. The Univariate analysis and the multivariate analysis have been used for screening prognostic risk factors. A nomograph has been constructed according to Cox proportional hazard regression models. A new score models has been constructed by analyzing receiver operator characteristic curve (ROC curve) and comparing with other clinical indexes. Results. Multivariate analysis displayed that tumor size, portal vein tumor thrombosis, adjacent tissue infiltration, microvascular infiltration, fibrinogen and total bilirubin were independent prognostic factors. The new scoring system has a higher AUC value than the other scoring systems, and the C index of the model is used to evaluate the survival rate of HCC patients in the validation group and the training group. Conclusions. Based on serum markers and other clinical indicators, we have established an accurate model to predict the HCC patients’ prognosis after radical surgery. Our scoring system can be helpful for the surgeons and the patients.